P186 Early and sustained responses with anifrolumab in patients with systemic lupus erythematosus (SLE) in 2 phase 3 trials. (23rd March 2020) - Morand, Eric F; Furie, Richard; Bruce, Ian; Kalunian, Kenneth C; Kalyani, Rubana N; Abreu, Gabriel; Pineda, Lilia; Tummala, Raj
Abstract : Background: In the phase 3 TULIP-2 and TULIP-1 trials in SLE, anifrolumab treatment increased the percentages of patients with BICLA responses vs placebo at Week 52 (Morand et al, 2020; Furie et al, 2019). To better understand the time course of BICLA responses to anifrolumab, we examined responses over time in TULIP-2 and TULIP-1, including sustained responses. Methods: The TULIP-2 and TULIP-1 randomized, double-blind, placebo-controlled trials evaluated anifrolumab (300 mg Q4W) over 52 weeks in patients with moderately to severely active SLE receiving standard-of-care treatment. Time to onset of BICLA response sustained from attainment through Week 52 was assessed. Results: At the first 3 assessments (Weeks 4, 8, and 12) in TULIP-2, numerically greater percentages of anifrolumab-treated patients (26.8%, 35.3%, and 42.9%, respectively; N=180) had a BICLA response compared with placebo (21.3%, 21.6%, and 31.8%; N=182). A similar trend was observed in TULIP-1 with anifrolumab (23.3%, 34.2%, and 36.5%; N=180) vs placebo (18.3%, 23.2%, and 27.5%; N=184). Time to onset of BICLA response in patients who achieved sustained BICLA response from onset through Week 52 in TULIP-2 (anifrolumab, n=86 [47.8%]; placebo, n=57 [31.3%]) and in TULIP-1 (anifrolumab, n=85 [47.2%]; placebo, n=55 [29.9%]) favored anifrolumab (HR=1.55, 95% CI 1.11–2.18 and HR=1.93, 95% CI 1.38–2.73, respectively; figure 1 ). Conclusions: Anifrolumab resulted in numerically favorable differences in BICLA responses maintained through Week 52, and in time to onset thereof, across TULIP studies. These data support the sustainability of clinical benefit with anifrolumab treatment in patients with active SLE.